Integrasi Islam dan Sains (Analisis Problematika dan Level Integrasi) - Egisca Mauly Sagita; Thasa Oktafiana; Tasya Aulia Arsul Masfufah; Oktaviani Putri Melinda; Alfina Wildatul Fitriyah (STIKes Ibnu Sina Ajibarang, 2024)
The separation of Islam and science resulted in the decline of Muslim civilization, on the one hand, and an existential crisis on the other. The integration of fatigue can lead Muslims to achievement as well as moral perfection. Efforts to integrate Islam and science have been initiated by Muslim thinkers through the dewesternization of science, the Islamization of science, the science of Islam, and others. Lagging behind in the fields of science and technology is a problem that has emerged since the end of the Middle Ages (18th century AD), so that since then Muslims have been infected with